Announcements
This discussion is closed.
Thread starter 14 years ago
#1
(x - 1)/(2x - 1) = (3x + 2)/(x+1)

I seem to be getting a different answer than the book. The book says x = 1.62, -0.62

Could someone please check if the book's right. Thank you.
0
14 years ago
#2
Sub the values into the expression to see if it is satisfied by the answer given in the book.
0
14 years ago
#3
(Original post by [email protected])
(x - 1)/(2x - 1) = (3x + 2)/(x+1)

I seem to be getting a different answer than the book. The book says x = 1.62, -0.62

Could someone please check if the book's right. Thank you.
No the book is wrong. I get x to be

1/10[-1 +/- rt(21)].
~= -0.56, 0.36

Is that what you got too?

Galois.
0
Thread starter 14 years ago
#4
(Original post by Gaz031)
Sub the values into the expression to see if it is satisfied by the answer given in the book.
It's rounded off to two d.p
0
Thread starter 14 years ago
#5
(Original post by Galois)
No the book is wrong. I get x to be

1/10[-1 +/- rt(21)].
~= -0.56, 0.36

Is that what you got too?

Galois.
I got:

(3+/- rt109) / 10

~= 1.34 or -.074
0
14 years ago
#6
(Original post by [email protected])
I got:

(3+/- rt109) / 10

~= 1.34 or -.074
(x - 1)/(2x - 1) = (3x + 2)/(x+1)

=> (x-1)(x+1) = (3x+2)(2x-1)
=> x^2 - 1 = 6x^2 + x - 2
=> 5x^2 + x - 1 = 0

=> x = 1/10 . [-1 +/- rt(21)]

Galois.
0
Thread starter 14 years ago
#7
If you mutiply through by (2x-3)(x+1), you get:
(x-1)(x+1) = (3x+2)(2x-1)
0
14 years ago
#8
(Original post by [email protected])
If you mutiply through by (2x-3)(x+1), you get:
(x-1)(x+1) = (3x+2)(2x-3)
But you had written (2x-1), not (2x-3).

Galois
0
14 years ago
#9
(Original post by [email protected])
(x - 1)/(2x - 1) = (3x + 2)/(x+1)

I seem to be getting a different answer than the book. The book says x = 1.62, -0.62.
(x - 1)/(2x - 1) = (3x + 2)/(x+1)
---> (x - 1)(x + 1) = (3x + 2)(2x - 1)
---> x^2 - 1 = 6x^2 + x - 2
---> 5x^2 + x - 1 = 0
---> x = {-1(+/-)Sq.rt[1 - 4(5)(-1)]}/10
---> x = {-1(+/-)Sq.rt(21)}/10
---> x = [-1 + Sq.rt(21)]/10 = 0.358...
---> x = -0.558...
0
14 years ago
#10
If the question was

(x - 1)/(2x - 1) = (3x + 2)/(x+1)

then x = 1/10 . [-1 +/- rt(21)]
________________________________ ___

If the question was

(x - 1)/(2x - 3) = (3x + 2)/(x+1)

then x = 1/2 . [1 +/- rt(5)]
________________________________ ___

Galois.
0
Thread starter 14 years ago
#11
(Original post by Galois)
But you had written (2x-1), not (2x-3).

Galois
Sorry, my mistake, the first one is right.
0
14 years ago
#12
x = 0.36 or x=-0.55

solved via quadratic formula 0
14 years ago
#13
(x-1)/(2x-1)=(3x+2)/(x+1)
(x-1)(x+1)=(3x+2)(2x-1)
(x^2)-1=(6x^2)-3x+4x-2
0=(5x^2)+x-1

Then use the quadratic formula to get:

x=0.358257569 or x=-0.558257569
0
X
new posts Back
to top
Latest
My Feed

Oops, nobody has postedin the last few hours.

Why not re-start the conversation?

see more

See more of what you like onThe Student Room

You can personalise what you see on TSR. Tell us a little about yourself to get started.

University open days

• University of Bradford
Thu, 24 Oct '19
• Cardiff University
Sat, 26 Oct '19
• Brunel University London
Sat, 26 Oct '19

Poll

Join the discussion

Yes (74)
24.1%
No (233)
75.9%